DESAIN BANGUNAN RUMAH TINGGAL SEDERHANA TANGGAP BENCANA BANJIR DI DESA FAHILUKA KABUPATEN MALAKA : - - Naikofi, Mauritius ildo Rivendi; Bees, Azarya; Hoar Siki, Yovinia Carmeneja; Pangu Loda, Januarya; Yansen Nurak, Eugenius; Benyamin Lily, Budy; Alfredo Abnit, Godefridus; Sabon Doni, Rikardus (LPPM Universitas Bina Bangsa, 2024)
Malaka Regency is one of the regencies that is often affected by floods every year. The losses caused by floods include, cutting off access to an area and damage to houses and furniture in the house, so that people have to evacuate to other areas or to higher ground. Incidents like this show that these houses have not been able to respond to floods that occur, including Fahiluka Village in Malaka Tengah District, Malaka Regency. The characteristic of Malaka Regency settlements is traditional houses in the form of stages with wooden walls and thatched roofs. Traditional stilt houses are also included in flood disaster response housing, but stilt houses have almost disappeared due to modern houses that are built directly in contact with the ground. This study aims to design a flood-responsive building model by utilizing modern building materials but still adhering to local wisdom. The results of the calculation and modeling of the flood that will occur with a return period of 25 years, obtained a maximum flood height of 2.5 meters. Building materials use reinforced concrete construction on the elements of the building structure and the shape of the building resembles a local building model and the function of the building space is adjusted to the needs of the community, the area of ​​the house designed is 54 m2. The design of the building with a stilt house model is expected to be one of the solutions in minimizing losses due to the overflow of the flood community that cannot be avoided in the Fahiluka village area.